ANALISIS PENERAPAN PRINSIP HACCP DAN IMPLIKASINYA TERHADAP MUTU GIZI PRODUK OLAHAN LAUT UMKM DI KENJERAN SURABAYA - Sari, Meirna Dewita; Saputro, Andre Ridho; Rahmatari, Bandaru (JURNAL SVASTA HARENA RAFFLESIA, 2025)
Seafood-based micro, small, and medium enterprises (MSMEs) play a vital role in the local economy of Kenjeran, Surabaya, yet many still lack sufficient knowledge of food safety systems. This study aimed to assess the understanding of MSME actors regarding the seven principles of the Hazard Analysis and Critical Control Points (HACCP) system and its implications for the nutritional quality of processed seafood products. A quantitative descriptive method was used, involving 24 closed-ended questionnaire items distributed to seafood-processing MSMEs in Kenjeran through purposive sampling. The research was conducted from January to March 2025. The instrument was validated through expert review and tested using Pearson correlation and Cronbach’s Alpha for reliability (α = 0.93). Data analysis employed descriptive statistics to identify patterns of understanding across HACCP principles. Results showed that overall comprehension was moderate, with the highest mean score on Principle 6 (Verification: 3.36), followed by Principles 2, 3, 4, and 7. However, Principle 1 (Hazard Analysis: 2.97) and Principle 5 (Corrective Actions: 2.98) had the lowest average scores, indicating critical gaps in recognizing food hazards and responding to deviations. These weaknesses may negatively impact the nutritional quality of seafood products, including protein degradation and vitamin loss due to poor control measures. It is recommended that targeted technical training, expert mentoring, improved documentation systems, and government support be implemented to enhance HACCP adoption. Strengthening food safety practices in MSMEs not only ensures product quality but also increases competitiveness in both local and global markets.